2015
DOI: 10.1021/acs.molpharmaceut.5b00233
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Delivery of Structurally Diverse Protein Cargo into Mammalian Cells by a Bacterial Toxin

Abstract: Platforms enabling targeted delivery of proteins into cells are needed to fully realize the potential of protein-based therapeutics with intracellular sites-of-action. Bacterial toxins are attractive systems to consider as templates for designing protein transduction systems as they naturally bind and enter specific cells with high efficiency. Here we investigated the capacity of diphtheria toxin to function as an intracellular protein delivery vector. We report that diphtheria toxin delivers an impressive arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 56 publications
1
51
0
Order By: Relevance
“…Targeting intracellular targets with protein-based inhibitors is currently not a therapeutic option due to the practical limitations of immunogenicity and the lack of efficient means for delivering proteins in to cells in vivo. However, progress continues to be made on methods for intracellular delivery of mRNA or proteins [30][31][32], and strategies to reduce immunogenicity, including the use of mirror-image proteins [33], have been developed. Thus, in the future, we are hopeful that UbVs may become bona fide drug candidates, but at present, they are best viewed as tool compounds that can enable drug discovery.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting intracellular targets with protein-based inhibitors is currently not a therapeutic option due to the practical limitations of immunogenicity and the lack of efficient means for delivering proteins in to cells in vivo. However, progress continues to be made on methods for intracellular delivery of mRNA or proteins [30][31][32], and strategies to reduce immunogenicity, including the use of mirror-image proteins [33], have been developed. Thus, in the future, we are hopeful that UbVs may become bona fide drug candidates, but at present, they are best viewed as tool compounds that can enable drug discovery.…”
Section: Discussionmentioning
confidence: 99%
“…Amylase is the only enzyme known to digest Lafora bodies. We have already shown that we are able to deliver amylase to cells in culture in this fashion and that amylase remains functional after crossing the cell membrane (Auger et al ., ). This disease, which we are particularly familiar with, exemplifies the immense possibilities ahead for all our patients with any form of PME.…”
Section: Protein Replacement Therapymentioning
confidence: 96%
“…It was shown that the toxicity of this toxin can be completely eliminated by a point mutation, whilst retaining its translocation properties. Finally, it was shown that a cargo protein, almost of any size, can be attached to this toxin and co-delivered to cells (so far in cell culture experiments only) with maintained function of the delivered protein (Auger et al, 2015). There are other post-genetic era therapeutic approaches in the works, and indeed a lot of excitement that the expression of certain genes will follow Mendelian genetics.…”
Section: Protein Replacement Therapymentioning
confidence: 99%
“…DT consists of a catalytically-active A fragment (DTA) and a B fragment (DTB) that includes both a receptor binding domain (DTR) and a translocation domain (DTT). DTB alone can bind its surface receptor, the heparin-binding epidermal growth factor-like growth factor (HB-EGF), and transfer a wide range of protein cargos to the cell cytosol via a receptor-mediated endocytic mechanism (Auger et al, 2015). The introduction of two amino acid substitutions (K51E and E148K) into DTA resulted in a non-toxic, catalytically-inactive A-fragment, herein referred to as DTa.…”
Section: Rrsp Into Cellsmentioning
confidence: 99%
“…Assessing the therapeutic potential of RRSP is however precluded by the fact that RRSP is a 56-kDa domain of a larger protein toxin that alone does not readily diffuse across biological Vidimar et al / Page 5 5 membranes, thus preventing its access to intracellular RAS. Recently, we demonstrated that the translocation machinery of diphtheria toxin (DT) can be engineered to deliver a broad diversity of passenger proteins into target cells (Auger et al, 2015;Park et al, 2018). In the present study, we exploit the receptor-targeting and membrane translocation properties of DT to deliver RRSP into target cells.…”
Section: Introductionmentioning
confidence: 99%